Effects of the Specific Eye Fixation Training on Fine Visuomotor Coordination in Children with Attention Deficit Hyperactivity Disorder - Valtr, Ludvík; Psotta, Rudolf; Dostál, Daniel (Children (Basel, Switzerland), 2023)
This study investigated the effects of quiet eye training (QET) on the neuropsychological functioning and fine motor performance of children with attention deficits. The participant cohort consisted of 106 children with attention deficit hyperactivity disorder (ADHD) between the ages of 8 and 12 years. The children were assigned to either the QET group (n = 54) or the control group (n = 52). The QET group went through a 5-week intervention in which the performance of blocks of targeting tasks was preceded by watching split-screen video footage featuring the gaze and body movements of a skilled model performing a throwing motion. Both groups underwent pre-test and post-test assessments, which included the reaction test of alertness, go/no-go inhibition test, and motor performance series test. The QET group demonstrated significant improvements in attentional engagement, inhibitory control, and fine motor skills, which require precise and fast visuomotor coordination. These results highlight the potential benefits of QET intervention in ameliorating attention deficits and enhancing fine aiming motor skills in children with ADHD. However, task specificity was evident, indicating that the intervention effects were most pronounced for the hand fine motor aiming tasks requiring both precision and speed.
Keywords: ADHD; children; intervention; attention; manual dexterity